factorise
4x² + 9Y² + 16z² + 12xy
- 24yz-16xz
Answers
Answered by
3
Step-by-step explanation:
4x²+9y²+16z²+12xy-24yz-16xz
=(2x)²+(3y)²+(-4z)²+2(2x) (3y) +(3y) (-4z) +(-4z) (-2x)
={2x+3y)+(-4z)}²
=(2x+3y-4z)²
=(2x+3y-4z) (2x+3y-4z)
Answered by
6
Answer:
explanation:
hope it you ✅✅✅✅thanks
Attachments:
![](https://hi-static.z-dn.net/files/dbc/853b092e5fe3ac5131cf6cc1df48f766.jpg)
Similar questions
Geography,
2 months ago
Social Sciences,
2 months ago
English,
5 months ago
Social Sciences,
5 months ago